Serological and molecular detection of Dirofilaria species in stray dogs and investigation of Wolbachia DNA by PCR in Turkey - Simsek, Sami; Ciftci, Ayse Turkan (Tehran University of Medical Sciences, 2016)
Background: Dirofilaria immitis and Dirofilaria repens are the most common species of filarial nematodes described in the dogs. A single-step multiplex PCR was applied to detect and differentiate simultaneously and unequivocally D. immitis and D. repens on DNA extracted from canine peripheral blood and besides to detect the seroprevalance of D. immitis by ELISA in Elazig Province, Turkey. A PCR detection of the Wolbachia, which plays an important role in D. immitis biology and contributes to the inflammatory pathology of the heartworm, was also applied for the first time in Turkey. Methods: A total of 161 whole blood and sera samples were collected from stray dogs and stored at -20 °C until used. After DNA extraction, all samples were processed with Dirofilaria primers by multiplex-PCR and Wolbachia primers by conventional PCR besides ELISA for serology. The amplification was performed using a set of primers designed on a portion of the small subunit ribosomal RNA gene of the mitochondrion (12S rDNA). Results: Three of the examined dogs (1.8%) were found to be infected with only D. immitis, one (0.6%) with D. repens and three (1.8%) with both parasites. Besides, 10 out of 161 dogs (6.2%) were found infected with Wolbachia sp. Finaly, the seroprevalence of dirofilariosis in the examined dogs was found to be 3.7% (6/161). Conclusion: Although dirofilariosis is not a serious problem in the region, the stray dogs still continue to be a source of infection.
Keywords: Dirofilaria immitis; Dirofilaria repens; ELISA; Multiplex-PCR; Wolbachia